Intensity‐modulated radiotherapy for early‐stage glottic cancer. (18th June 2015) - Berwouts, Dieter; Swimberghe, Martijn; Duprez, Fréderic; Boterberg, Tom; Bonte, Katrien; Deron, Philippe; De Gersem, Werner; De Neve, Wilfried; Madani, Indira
Abstract: Background: The purpose of this study was to report on treatment outcome of intensity‐modulated radiotherapy (IMRT) for early‐stage (cT1–2 cN0 M0) squamous cell carcinoma of the glottis, as compared with patients treated with conventional radiotherapy. Methods: Between November 2007 and December 2011, 40 consecutive patients were treated with IMRT with daily cone‐beam CT position verification. The median prescription to the planning target volume (PTV) was 63 Gy/28 fractions and 67.5 Gy/30 fractions for T1 and T2 tumors, respectively. The historical control comprised 81 consecutive patients treated with conventional radiotherapy to total doses of 66 Gy/33 fractions (66 patients) and 70 Gy/35 fractions (15 patients) for T1 and T2 tumors, respectively. Results: The median follow‐up of living patients was 3.8 years (range, 1.0–5.0 years) in the IMRT group and 9.0 years, (range, 5.2–12.7 years) in the conventional group. Five‐year actuarial local control was equal compared to the conventional group: 83% versus 74% ( p = .64). Five‐year actuarial ultimate local control was 100% in the IMRT group and 95% in the conventional group ( p = .17). Five‐year actuarial overall and disease‐specific survival was 85% after IMRT versus 65% after conventional radiotherapy ( p = .15) and 97% versus 89% ( p = .31), respectively. Incidence and severity of acute dermatitis was significantly less during IMRT than in the control group ( p < .001). Two patients receiving IMRT had late grade 3 hoarseness. Conclusion: IMRT is as efficient as conventional radiotherapy in terms of disease control and overall survival. It has the potential to reduce toxicity as compared to conventional radiotherapy. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E179–E184, 2016